Kiprah Muhammadiyah dalam Pemberdayaan Masyarakat Desa - Ucin Muksin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2015)
As a socio-religious organization that has a strong attention to the paradigm of education in the country, Muhammadiyah a mouthpiece for membuminya moral and ethics in society. For Muhammadiyah, education is not only to educate students and the community to be clever, but more importantly how the educational values integrated into the social and religious values. Departing from this fact, this study is directed to look at the lunge, the organization Muhammadiyah in District Bojonggede the "guests" in the community that embraces the philosophy of Ahl al-Sunnah wal-Jama'ah al in an effort to build a people-based education as a form of achievement of civil society (main) in accordance with the vision and mission of Muhammadiyah movement.